AN X-RAY DIFFRACTION AND INFRARED SPECTROSCOPY STUDY OF TWO TYPES OF ZEOLITES SATURATED WITH ZN - Al-Mashhdany, M.A. R.; Al-Hadethi, A. A. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This research was included a method for preparing synthetic zeolite using araw clay mineral components found in nature (kaolin) and it was prepared by the hydrothermal method in the presence of sodium hydroxide. Natural zeolites were also used and saturated with zinc adopting the method of columns through ZnSO4.7H2O solution. Several measurements were taken for the zeolites before and after the saturation process, the results obtained were ascribed to the X-ray diffraction (XRD) which showed a well crystallization rate while the chemical analysis of the elements showed that they contain a high percentage of silicon and aluminum, which gives evidence, is a balanced and equal reaction. The infrared spectrum (IR) showed the change in the frequency band of 1002 cm-1, which expresses its sensitivity to the occurrence of the substitution process within the structural composition of the zeolite, and confirmation of this is the disappearance of the weak shoulder from the right side of the diffraction 1002 cm-1, which represents the voids in the structural composition of the mineral, which was accompanied by the widening of the diffraction itself, it confirms the occurrence of replacement of zinc in those voids.